Global Health Security and Weapons of Mass Destruction Chapter - Reynolds, Chris (Global Health Security, 2019)
The global proliferation of weapons of mass destruction (WMD) presents a clear and present danger to global health security. Unlike conventional weapons that confine themselves to a defined and targeted area, WMD’s cross international boundaries and borders. Moreover, the release of WMDs can be achieved using a low technology approach resulting in a transformation and redefinition of the mission of global health providers. This chapter will focus on the ease of access to WMDs, the impact biological weapons and bioterrorism plays on global health security, United States global policies on public health, and the role actors and non-state actors play in the global health landscape. In addition, this chapter will focus on global WMD proliferation prevention to include international efforts, treaties, and conventions. The chapter will conclude with a discussion of ongoing research initiatives, identification of emerging threats, and additional recommended readings.